Goals of care discussions among critically Ill patients on vasopressor treatment - Walid A. Alkeridy; Khalid M. Alayed; Shadan AlMuhaidib; Mohammed Khalid Alageel; Sarah Ahmed Alqahtani; Shatha Bin Dher; Abdulaziz M Almotairi; Claire Ann Lim; Musa F. Alzahrani (PLoS ONE, 2025)
Background Goals of care (GOC) discussions are essential for aligning medical management with the values of critically ill patients, particularly those requiring vasopressors, such as dopamine. To evaluate GOC discussions in terms of prevalence, factors associated with documentation, and impact on survival among critically ill patients requiring vasopressors for hemodynamic support. Methods We conducted a retrospective cohort study at a tertiary healthcare facility in Riyadh, Saudi Arabia, focusing on patients admitted to intensive care units (ICUs) and internal medicine (IM) wards. The study included adult in patients who received dopamine during their hospital stay. Factors associated with GOC documentation were identified using logistic regression analysis. The 30-day and 1-year survival rates according to GOC discussions were analyzed using Kaplan–Meier survival curves, which were compared using the log-rank test. Results Of 301 patients, 56.8% were men and 64.8% were aged ≥60 years. GOC discussions were documented in 61.8% of patients and were more frequent among older patients (≥60 years) than among younger patients (73.1% vs. 51.3%, p < 0.001) and in those with higher APACHE II scores (median 21.0 vs. 18.0, p = 0.001). Multivariable analysis identified age ≥ 60 years as independent precipitating factor of GOC discussions (odds ratio 2.41, 95% confidence interval 1.34–4.32, p = 0.003). The study found significantly lower survival rates at both 30 days and 1 year among patients who had documented GOC discussions. Conclusions GOCs were more prevalent among critically ill older patients. The study found significantly higher mortality rates at both 30 days and 1 year among patients who had documented GOC discussions. These findings highlight the need for institutional strategies to integrate GOC discussions into routine care and address their potential implications on patient outcomes.